Effects of periodontal therapy on GCF cytokines in generalized aggressive periodontitis subjects - Oliveira, APL (2011)
AIM: To examine changes in levels of gingival crevicular fluid (GCF) cytokines, after periodontal therapy of generalized aggressive periodontitis (GAgP). MATERIALS AND METHODS: Twenty five periodontally healthy and 24 GAgP subjects had periodontal clinical parameters measured and gingival crevicular fluid (GCF) samples collected from up to 14 sites/subject. GCF samples were analyzed using multiplex bead immunoassay for: GM-CSF, IFN-γ, IL-10, IL-1β, IL-2, IL-6 and TNF-α. Aggressive periodontitis subjects were randomly assigned to either scaling and root planing (SRP) alone or SRP plus systemic amoxicillin (500 mg) and metronidazole (400 mg) 3 times a day for 14 days. Clinical parameters and GCF cytokines were re-measured 6 months after treatment. Differences over time were analyzed using the Wilcoxon test and between groups using the Mann-Whitney test. RESULTS: Significant reductions in GCF GM-CSF, IL-1β and the ratio IL-1β/IL-10 and increases in GCF IL-6 were detected after therapy. The mean change in GCF cytokines did not differ significantly between groups. CONCLUSIONS: Periodontal therapy improved GCF cytokine profiles by lowering IL-1β and increasing IL-10 levels. The reduction in GCF GM-CSF after therapy implicates this cytokine in the pathogenesis of GAgP. There was no difference between therapies in changes of GCF cytokines.